2018
DOI: 10.3847/1538-4357/aaccf1
|View full text |Cite
|
Sign up to set email alerts
|

On the Variability of the Solar Mean Magnetic Field: Contributions from Various Magnetic Features on the Surface of the Sun

Abstract: The solar mean magnetic field (SMMF) is referred to as the disk-averaged line-of-sight (LOS) magnetic field that also reflects the polarity imbalance of the magnetic field on the Sun. The origin of the SMMF has been debated over the past few decades, with one school of thought suggesting that the contribution to the SMMF is mostly due to the large-scale magnetic field structure, also called the background magnetic field, whereas other and more recent studies have indicated that active regions have a major cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…It has contribution from both the large scale magnetic field structure (i.e., ambient magnetic field) and the active regions on Sun. In recent study Bose & Nagaraju (2018) have shown that the variations in solar magnetic field has major (89%) contribution from the ambient magnetic field and the contribution from other features is insignificant (11%). It may be noted that SMED has undergone considerable gradual decrease from SC 22 to SC 24 (it is discussed in Sect.…”
Section: Data Sets and Energy Estimatesmentioning
confidence: 99%
“…It has contribution from both the large scale magnetic field structure (i.e., ambient magnetic field) and the active regions on Sun. In recent study Bose & Nagaraju (2018) have shown that the variations in solar magnetic field has major (89%) contribution from the ambient magnetic field and the contribution from other features is insignificant (11%). It may be noted that SMED has undergone considerable gradual decrease from SC 22 to SC 24 (it is discussed in Sect.…”
Section: Data Sets and Energy Estimatesmentioning
confidence: 99%
“…This resulted in a binary mask in which 1 corresponded to the pixels of interest, and 0 the rest. This minimum chosen value of the magnetic flux density is close to the noise level of the HMI_720s magnetograms (Liu et al 2012;Bose & Nagaraju 2018). Finally, we used this mask to extract the cospatial quiet-Sun (less active) pixels from each AIA channel and computed the respective 1D histograms of the intensity values as shown in Fig.…”
Section: Baseline Modelmentioning
confidence: 96%
“…Especially it is seen in areas of dark spots [29]. According to numerous data, B 0 has a value of several gauss (see, for example, [30] and references therein). (In this paper, we will assume B 0 ∼ 10 G for estimates.)…”
Section: Convection In Astrophysicsmentioning
confidence: 99%